2009
DOI: 10.1080/00365520902998679
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of HLA class I antigen-processing machinery components in esophageal squamous cell carcinomas: Association with disease progression

Abstract: Our results indicate that lack or reduction of HLA class I antigens and expression of APM components in ESCC may render some tumor cells to escape the immunosurveillance mediated by CD8(+) T cells and contribute to the clinical course of ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 29 publications
6
27
0
1
Order By: Relevance
“…Relapse-free survival increased significantly in the MHC class I-positive patients compared to the negative patients in the total patient group and the chemotherapy-only group, but not in the PSK group. PSK, protein-bound polysaccharide K. prognosis have been reported to be correlated in various types of cancer, including breast, lung, renal cell carcinoma and colon cancer (8,9,(17)(18)(19). The present study found that the expression rate of MHC class I in primary gastric cancer lesions was 55%, close to the values that have been reported in other studies (20).…”
Section: Correlation Between Expression Of Mhc Class I and Efficacy Osupporting
confidence: 79%
See 2 more Smart Citations
“…Relapse-free survival increased significantly in the MHC class I-positive patients compared to the negative patients in the total patient group and the chemotherapy-only group, but not in the PSK group. PSK, protein-bound polysaccharide K. prognosis have been reported to be correlated in various types of cancer, including breast, lung, renal cell carcinoma and colon cancer (8,9,(17)(18)(19). The present study found that the expression rate of MHC class I in primary gastric cancer lesions was 55%, close to the values that have been reported in other studies (20).…”
Section: Correlation Between Expression Of Mhc Class I and Efficacy Osupporting
confidence: 79%
“…In esophageal cancer, MHC class I expression in metastatic lymph nodes was found to be depressed compared to that in the primary lesion (9). That is, cancer cells that have evaded the host immune response are considered to be able to readily form metastatic foci in the lymph nodes.…”
Section: Correlation Between Expression Of Mhc Class I and Efficacy Omentioning
confidence: 99%
See 1 more Smart Citation
“…33 Previous study indicated that downregulation of HLA class I molecules in the tumor was associated with a poor prognosis in esophageal squamous cell carcinoma (ESCC) patients and defects of HLA class I antigen-processing machinery components, including b 2 -microglobulin (b 2 m), transporters associated with antigen presentation (TAP)1, large multifunctional proteasome (LMP) 2 and LMP7, in ESCC patients was related to disease progression. 34,35 However, little information was available for the clinical relevance of HLA-G, both the primary tumor HLA-G expression and sHLA-G in plasma in particular, in ESCC. An early study indicated that HLA-G expression was associated with a poor survival in ESCC patients.…”
mentioning
confidence: 99%
“…An association between the downregulation of TAP-1, TAP-2 and HLA-I expression and cancer prognosis has been reported in a wide range of malignancies (21)(22)(23)(24). The correlation between TAP-1, TAP-2 and HLA-I and prognosis in NPC has been investigated (25).…”
Section: Discussionmentioning
confidence: 99%